FAKTOR YANG MEMPENGARUHI PREFERENSI REMAJA BALI DALAM KEINGINAN MEMILIKI JUMLAH ANAK IDEAL - Krismayanthi, I Gusti Ayu Agung Putri; Marfianti, Istiana; Indrayathi, Putu Ayu; Listiani, Ni Made Ari (ARCHIVE OF COMMUNITY HEALTH; Vol 7 No 2 (2020): Desember 2020DO - 10.24843/ACH.2020.v07.i02.p10, 2020)
ABSTRACT In the 2017 Indonesian Demographic and Health Survey (SDKI), found that a decrease in TFR from 2.60 children per woman to 2.4 children per woman and still had not reached the national target in 2018 of 2.31 children per woman. Bali Province is one of the provinces with the lowest TFR of 2.2 children per woman. The purpose of this study is to determine the factors that influence the preferences of Balinese adolescents to have the ideal number of children. This study is a secondary data analysis from the 2018 KKBPK Program Performance and Accountability Survey (SKAP) with a cross-sectional design. The sample size was 632 unmarried adolescents aged 15-24 years consisting of 334 female adolescents and 298 male adolescents. The variables studied were gender, age, place of residence, education, wealth quintile, adolescent exposure to reproductive health information and sources of population information with the dependent variable being the desire of the family to have many children (> 2). Based on sex, as many as 58.5% of adolescent girls aged 15-24 years prefer to have many children (>2) compared to boys (41.4%). The results of multivariate analysis showed significantly related factors namely gender (p = 0.014, OR = 1,722, 95% CI = 1,115-2,593) and television (p = 0.043, OR = 1,729, 95% CI = 1,017-2,937). While the protective factor is pamphlets / brochures / leaflets (p = 0.002, OR = 0.444, 95% CI = 0.265-0.747). The conclusion that can be drawn in this study is the preference of Balinese adolescents in their desire to have an ideal number of children influenced by internal factors such as gender and external namely mass media such as television.